SIMULATING THE LOGISTIC PROCESS REDESIGN OF MATERIAL PLANNING IN UPSTREAM OIL AND GAS INDUSTRIES CASE STUDY HUSKY CNOOC MADURA LIMITED 2016 - Bobby, Caesar Ramos; Handayati, Yuanita (Journal of Business and Management, 2018)
Abstract. This research will examine the logistic process that usually applied by the upstream oil and gas company by looking inside the Husky CNOOC Madura Limited (HCML) and how the problem of huge amount of excess material and dead material may happen when the company planned the material that will be needed. By using the theoretical framework of BPMNÂ  to know why the problem of excess material and dead stock may happen when planned the material, it need to be check by looking into the logistic process, because of that this research will be focus on the logistic process, which to looking the logistic process it need to look into the system of logistic in the company and understandingÂ  the integration of the system and its process, because the logistic process are the modeling of the system that applied by company. Based on that this research will be take look in the area of order processing and inventory control, to know how the logistic process of the material planning are applied by company. Husky CNOOC Madura Limited (HCML) is one of the production sharing contractor in the upstream oil and gas industries which stand in 2011, this company engaged in the upstream oil and gas industry which the company are based on Jakarta and conduct the production on the Madura strait block. Like most of other companies or contractors which engaged in the upstream industries, the activities that engaged in company was helped by using the third-party provider. Some of the problem appear in logistic when using the third parties are the lack of management in buying material or planning the material that will needed, and because this lack it usually made the excess material and dead stock that make a loss to company and HCML also already done some improvement to reduce the problem cause but it still not satisfies the company, because of that to more optimize the improvement, now HCML want to redesign its logistic process . Findings on this research was found that the problem of excess material and dead stock may happen when planning the material because the company applied an anomaly for their system and the integration which in their system they applied the pull system and for their integration it applied the MRP which the origin of MRP are the push system. Because of that it made the logistic process become distracted and not completed. Based on this research if the company want to applied the system and the integration like that it need to explain in the logistic process, to avoid the problem of excess material and dead stock happened. Keyword: Logistic Process, Excess Material, Dead Stock, HCMLÂ